An Industry Perspective on Smart Cities: A Smart City Process Framework - Rondon, Márcio Egydio S.; Fonseca, Fabio L.; Maximo, Andre; Costa, Felipe M.; Macía, Isela; Rodrigues, Paulo G.; Blois, Marcelo (Anais do Seminário Integrado de Software e Hardware (SEMISH); 2013: Anais do XL Seminário Integrado de Software e Hardware, 2013)
The smart city domain is receiving a lot of attention from the software community around the globe. The reason is that city population is growing in fast pace and new solutions and software techniques are required to enhance citizens' quality of life and avoid a city breakdown. This paper proposes a process framework to clarify the main processes of a smart city and, therefore, pave the way for applying software knowledge into the smart city domain. Based on this framework, we derive a classification system to improve the understanding of current smart city projects. In this system, each category represents an instance of the framework. Finally, we classify smart city projects using the envisioned system, as an example of its utilization.